Protection And Legal Accountability On Online Healthcare Application In The Perspective Of Legal Certainty - Maharani, Andita; A, Kolib; Bakhtiar, Handar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This research aims to analyze legal protection arrangements and legal accountability on online-based health care applications in the perspective of legal certainty. The research approach used is a normative legal research approach with primary, secondary and tertiary sources of data or legal materials. In this research, the analysis carried out used qualitative research methods and generates data that was descriptive or not quantitatively measurable. The results of the research show that legal protection arrangements are subject to and must comply with UU No. 17 of 2023 concerning Health, UU No. 19 of 2016 concerning Amendments to UU No. 11 of 2008 concerning Electronic Information and Transactions, and related laws and regulations. Patients have the right to obtain legal protection when obtaining health services using an online-based health care application. Legal liability for online-based health service applications does not yet have regulations that specifically regulate legal certainty regarding the resolution of problems when the application experiences errors or system failures that result in losses for users, for both doctors and patients.